Edukasi Sari Kacang Hijau Untuk Mengatasi Anemia Pada Ibu Hamil Di Desa Sukapura Kecamatan Sragi Kabupaten Lampung Selatan Tahun 2024 - Primadevi, Inggit; Anisah, Aan; Arti, Widi; Dewi, Dian Cynthia; Rohmawati, Rohmawati; Oktapiana, Putri Dian; Wulandari, Anna Dwi; Dewi, Rahmi; Trisnawati, Budi; Zannah, Miftahul (Universitas Pahlawan Tuanku Tambusai, 2024)
The maternal mortality rate (MMR) is an indicator of the success of health services in Indonesia. Maternal death can occur due to anemia. The maternal mortality rate shows that the maternal mortality rate is 70% for anemic mothers. Anemia in pregnancy is also associated with increased maternal morbidity (Amalia, 2018). Anemia that commonly occurs during pregnancy is iron deficiency anemia. Iron (Fe) during pregnancy. Another way to reduce the incidence of anemia in pregnant women is not only to give Fe tablet supplements, but to be supported and assisted by providing food intake that is rich in iron. One type of legume that contains high iron is green beans. Green beans contain substances necessary for the formation of blood cells so they can overcome the effects of decreasing hemoglobin (USDA, 2016). The aim of this outreach to the community is to provide information and knowledge through educational outreach programs by carrying out preventive and promotive efforts to prevent and treat anemia in pregnant women. Counseling was carried out in Sukapura Village, Sragi District, South Lampung Regency in the Sragi Health Center Working Area. with a distance of 113 km from Aisyah Pringsewu University. Many health problems occur in the Puskesmas area. One of the health problems that must be addressed is anemia in pregnant women. So with this activity it is hoped that the community, especially pregnant women, will be able to understand and realize the importance of knowledge of green bean juice in overcoming anemia.